PP.01 Perinatal Outcome of IUGR Pregnancies with Normal and Abnormal Doppler Studies – The Prospective Multicentre Porto Trial. (26th April 2013) - Unterscheider, J; Daly, S; Geary, MP; Kennelly, MM; McAuliffe, FM; O'Donoghue, K; Hunter, A; Morrison, JJ; Burke, G; Dicker, P; Tully, EC; Malone, FD
Abstract : Objective: The objective of this analysis, as part of the multicentre prospective PORTO Trial, was to describe and compare perinatal outcomes of IUGR pregnancies with normal and abnormal umbilical artery (UA) Doppler studies. Study design: The PORTO Trial recruited over 1, 100 consecutive ultrasound-dated singleton IUGR pregnancies, defined as EFW < 10 th centile. All fetuses underwent serial sonographic assessment until birth. Perinatal outcomes were documented for all participants. Results: Of the 1, 118 recruited patients, 606 (54%) had normal UA Doppler studies and 512 (46%) had abnormal UA Dopplers, defined as UA PI > 95 th centile or AREDF. The group with abnormal UA Doppler was delivered earlier and more commonly by CS, had more admissions to NICU and adverse perinatal outcomes (Table 1 ). The 4 mortalities with normal Doppler all had EFW < 3 rd centile. Conclusion: IUGR fetuses with normal UA Doppler studies have better perinatal outcomes than those with abnormal UA Doppler, however adverse perinatal outcome can occur with normal UA in more severe IUGR cases (EFW < 3rd centile).